Improving the teaching of globe and map skills in the elementary school - Luis, Lidinila M. 1936- (1969)
A content analysis of the different literature on the subject of globe and map skills was made. The abilities that need to be developed in globe and map skills are the following: ability to orient the map and note directions, locate places on maps and globes, use scale and compute distances, interpret map symbols and visualize what they represent, and to compare maps and draw inferences. The researcher observed that the lack of maps and globes in the public schools can be partly solved by making intelligent use of the available resources. It will be a matter of knowing the sources of these materials, exerting efforts to obtain the same and then making full use of whatever materials are received.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Elementary) -- Philippines; Geography -- Study and teaching (Elementary) -- Philippines; Map reading -- Philippines; Globes